Study of the Weber number impact on secondary breakup of droplets of coal water slurries containing petrochemicals; Fuel; Vol. 254 - Minakov A. V. Andrey Viktorovich; Shebeleva A. A. Anna Andreevna; Strizhak P. A. Pavel Alexandrovich; Chernetsky M. V. Mikhail Yurjevich; Volkov R. S. Roman Sergeevich (2019, 2019)
Title screen